Using stage frequency distributions as objective functions for model calibration and global sensitivity analyses. (June 2017) - Lindenschmidt, Karl-Erich
Abstract: A novel approach is presented for model calibration and global sensitivity analyses in which stage frequency distributions (SFD) are used as objective functions, not single values or time series, for example water levels or flows, which are traditionally used in hydraulic and hydrological modelling. This allows the stochastic nature of the input parameter to be characterised which is an important feature for some hydraulic processes of northern rivers such as ice jam formation. The observation SFD can also be used as part of an objective function for global sensitivity analysis, also a novelty presented in this paper, to determine the sensitivity of input parameter and boundary condition frequency distributions on different flooding regimes.